Experiences of Healthcare Staff Regarding Angiography in Infants - Haydeh Heidari; Arsalan Khaledifar (Mashhad University of Medical Sciences, 2021)
Background: Nowadays, the promotion of cardiac care programs for infants in need of specialized heart care has improved the survival of these patients. This study aimed to explain the experiences of healthcare staff regarding angiography in pediatric patients. Methods: This study was conducted based on qualitative content analysis. The data were collected through in-depth, semi-structured, face-to-face, and individual interviews. In total, 20 participants (9 nurses, 4 radiologists, and 7 pediatric cardiologists) were included in this study. Results: According to the results, three main categories were found in this study, including the need for specialized skills (along with three subcategories of the need for knowledge skills, communication skills, and experience), lack of pediatric angiography facilities (along with three subcategories of a shortage of specialist and pediatric nurses, as well as lack of space), and lack of providing care to caregivers (along with three subcategories of intensive shifts, suffering from aggressive pediatric procedures, and environmental vulnerability). Conclusion: Health care staff working in the field of angiography in infants are experiencing numerous mental and psychological problems; however, the health system has not taken supportive measures for such personnel. The result of this study can help future interventions develop supportive programs for healthcare staff working in this unit.